Essentials of retirement planning : a holistic review of personal retirement planning issues and employer-sponsored plans - Robbins, Eric J. (Finance and financial management collection., 2015)
This book provides the quintessential information needed to understand the financial side of the retirement planning coin. You'll begin by learning about the various plan types employers may offer their employees. Topics related to compliance testing as well as the strategies used to legally shift benefits in favor of highly compensated employees will be thoroughly discussed. However, some employers do not sponsor a plan. In this instance, retirement savers will need to understand the options available within the world of individual retirement accounts. This book is not intended to provide investment advice, but rather to show how different retirement savings vehicles function and how they can be effectively deployed. Many financial professionals find that their clients ask questions about all aspects of their financial life. For this reason, this book also discusses noninvestment-related topics such as housing options, Social Security planning, Medicare planning, and a few other basic insurance-based issues faced by all retirees.